Barnacle cement protein as an efficient bioinspired corrosion inhibitor - Bui, My Hanh (2024)
To prevent corrosion damage in aggressive environments such as seawater, metallic surfaces are coated with corrosion inhibitors usually made of organic molecules. Unfortunately, these inhibitors often exhibit environmental toxicity and are hazardous to natural habitats. Thus, developing greener and effective corrosion inhibitors is desirable. Here, we present an alternative green inhibitor, the recombinant protein rMrCP20 derived from the adhesive cement of the barnacle Megabalanus rosa and show that it efficiently protects mild steel against corrosion under high salt conditions mimicking the marine environment. We reveal that these anti-corrosion properties are linked to the protein’s biophysical properties, namely its strong adsorption to surfaces combined with its interaction with Fe ions released by steel substrates, which forms a stable layer that increases the coating’s impedance and delays corrosion. Our findings highlight the synergistic action of rMrCP20 in preventing corrosion and provide molecular-level guidelines to develop alternative green corrosion inhibitor additives.